2017
DOI: 10.1242/dev.150664
|View full text |Cite
|
Sign up to set email alerts
|

Coup-TF1 and Coup-TF2 control subtype and laminar identity of MGE-derived neocortical interneurons

Abstract: Distinct cortical interneuron (CIN) subtypes have unique circuit functions; dysfunction in specific subtypes is implicated in neuropsychiatric disorders. Somatostatin-and parvalbuminexpressing (SST + and PV + ) interneurons are the two major subtypes generated by medial ganglionic eminence (MGE) progenitors. Spatial and temporal mechanisms governing their cellfate specification and differential integration into cortical layers are largely unknown. We provide evidence that Coup-TF1 and Coup-TF2 (Nr2f1 and Nr2f2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
80
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(89 citation statements)
references
References 55 publications
6
80
2
1
Order By: Relevance
“…The pattern of expression we observed here mirror descriptions of other studies of NR2F2 expression in the rodent hippocampus [22], as well as more macroscopically in the human brain during development, particularly in the temporal lobes [4]. NR2F2 is also key in the determination of cell fate in numerous circumstances [32, 27], including that of interneurons expressing PVALB (parvalbumin) or SST (somatostatin), where NR2F2 promotes SST and represses PVALB [27]. These findings are highly consistent with the expression of PVALB (expressed posteriorly) and SSTR1 (expressed anteriorly with NR2F2) in our data (Table 1).…”
Section: Discussionsupporting
confidence: 85%
“…The pattern of expression we observed here mirror descriptions of other studies of NR2F2 expression in the rodent hippocampus [22], as well as more macroscopically in the human brain during development, particularly in the temporal lobes [4]. NR2F2 is also key in the determination of cell fate in numerous circumstances [32, 27], including that of interneurons expressing PVALB (parvalbumin) or SST (somatostatin), where NR2F2 promotes SST and represses PVALB [27]. These findings are highly consistent with the expression of PVALB (expressed posteriorly) and SSTR1 (expressed anteriorly with NR2F2) in our data (Table 1).…”
Section: Discussionsupporting
confidence: 85%
“…S2A), and the regulation of Pax6 by MEIS1 has been independently validated recently (Owa et al 2018). The RA signal propagates further through PAX6 to activate interneuron-related genes Nr2f2 and Nr2f1 (Hu et al 2017). .…”
Section: Grn-loop Reveals Driver Tfs and Cis-regulatory Dna Elementsmentioning
confidence: 90%
“…This study suggests new ideas about how some aspects of CIN cell fate and function are regulated, particularly in post-mitotic/maturing CINs. Previous studies identified TFs that are expressed in SST+ CINs but not in PV+ CINs, as well as TFs that can alter the ratios of SST+ and PV+ CINs [22][23][24]27,[56][57][58] . Of note, we are not aware of a TF that is uniquely expressed in PV+ but not SST+ CINs 59 .…”
Section: Discussionmentioning
confidence: 99%